Hubungan antara Kemampuan Turn Taking dengan Kemampuan Sintaksis Anak Down Syndrome di Surakarta - Putri, Adelia Ardiningrum Riyanto; Sudarman, Sudarman (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Down syndrome is a genetic abnormality, leading to impaired intellectual development, caused by chromosomal abnormalities. Turn-taking is a fundamental aspect of the interaction because it is difficult to talk and Listen at the same time. Taking turns plays an important role in the communication process, as it can affect syntactic abilities. Objectives: This study aims to determine the relationship between turn-taking ability and syntactic ability of children with down syndrome in Surakarta. Methods: This study used a quantitative approach with a cross-sectional design. The sampling procedure applied was purposive sampling, with a total of 30 participants. The data obtained in this study were analyzed through univariate and bivariate methods. The statistical test used is the Spearman's Rank test. Results: The results of data analysis showed that the results of turn-taking ability in children with Down syndrome were mostly classified as adequate (60%) and the results of syntactic ability in children with Down syndrome were mostly classified as moderate (50%). The Spearman Rank test states that the value of ρ = 0.013 means that the value of ρ < 0.05 then Ha is accepted with a correlation (r) = 0.048 meaning that there is a positive correlation with the medium category. Conclusion: There is a relationship between turn-taking ability and syntactic ability in children with Down syndrome in Surakarta. Keywords: Down syndrome, Turn-taking ability, Syntactic ability